Biomarcadores imunológicos séricos e nasais na infecção pediátrica pelo vírus sincicial respiratório - Assumpção Neto, Erasmo (2020)
INTRODUCTION: Respiratory Syncytial Virus (RSV) is one of the main etiological agents responsible for Bronchiolitis, an acute respiratory infection that causes wheezing in children under 2 years of age. Pre-clinical studies have shown that pro-inflammatory cytokines, growth factors and chemokines are correlated with disease severity, symptom recurrence, asthma development, and / or chronic disease. Few studies have evaluated this inflammatory profile in clinical practice. OBJECTIVES: To analyze biomarkers of tissue aggression, pro and anti-inflammatory cytokines and the activation of innate immune response genes in pediatric RSV infection. METHODS: Quantify in children under 2 years of age, of both sexes, with RSV infection classified clinically as mild, and in a control group (neonates, both sexes), a profile of biomarkers and cytokines (ATP; IL1- BETA; IGF1; IL-13; IL-17; IL-23; IL1-RA; RELAXIN 1; IL-10; IL-5; IL-8; RELAXIN 3; VEGF; TSLP) in nasal secretion and blood, and check gene activation of the NLRP3 pathway and the P2X7 pathway in serum leukocytes. RESULTS: The Bronchiolitis Group, compared to the Control group, presented lower values of ATP, RELAXIN 1, RELAXIN 3, IL-23, IL-13, IL-5 and higher of IL-8 and IL-1RA in the nasal aspirate. Still, in serum dosages, the Bronchiolitis Group showed lower values of IL-1B and higher values of IL-23. There was no correction between the nasal and serum inflammatory response for the different biomarkers evaluated. There was no statistical difference between the groups in the expression of purinergic P2X7R receptor in leukocytes. However, less gene expression of NLRP3 occurred in the leukocytes of children with bronchiolitis when compared to the control. CONCLUSION: In pediatric patients under 2 years of age, with a clinical diagnosis of mild bronchiolitis, the inflammatory response seems to be restricted to the bronchopulmonary territory. We can infer that the immunomodulation caused by the greater amount of IL1-RA in the nasal secretion, can act suppressing the Th1, Th2 and Th17 pathways justifying the lower values of ATP, RELAXIN 1, RELAXIN 3, IL-23, IL-13 and IL- 5 in the nasal secretion caused by the respiratory syncytial virus. In addition, the inhibition of NLRP3 inflamosome in leukocytes could favor the reduction of IL-1β production systemically.